The Influence of Student Adaptability and Academic Self-Efficacy on Academic Buoyancy - Muhammad Haikal Nur; Nadya Novia Rahman; Ayunda Ramadhani (Green Publisher Indonesia, 2024)
This study aims to determine the effect of adaptibility and academic self-efficacy on academic buoyancy in students of the Faculty of Economics, University of X Samarinda. This research method using quantitative methods. The subjects of this study were 103 students of the Faculty of Economics, University of X Samarinda who were selected through simple random sampling technique. Data collection methods used are adaptibility scale, academic self-efficacy and academic buoyancy. The data analysis technique used is multiple linear regression analysis. The collected data were analyzed with the help of the Statistical Package for Social Science (SPSS) program version 26 for windows. The results of the study show that: (1) there is a significant effect of self-adjustment and academic self-efficacy on academic buoyancy with a calculated F value = 149,428 > F table 3.09 and p value = 0.000 and has an R2 influence contribution of 74.9%; (2) there is a significant effect of self-adjustment on academic buoyancy with a coefficient of beta (β) = 0.269, t count = 2.600 > t table 1.984 and p = 0.011 (p > 0.05); (3) there is a significant effect of academic self-efficacy on academic buoyancy with a coefficient of beta (β) = 0.621, t count = 6.001 > t table and p = 0.000 (p < 0.05).